SIFAT KIMIA TANAH DYSTRUDEPTS DAN PERTUMBUHAN AKAR TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) YANG DIAPLIKASI MULSA ORGANIK Mucuna bracteata - Ika Septina Sembiring; Wawan '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
One effort to improve chemical properties of Dystrudepts is to use an organic mulch Mucuna bracteata (MB). The study aims to determine the effect of application of organic mulch MB on soil chemical properties and plant root growth of oil palm. The research was conducted in experimental station and the soil laboratory, Faculty of Agriculture, Riau University, Pekanbaru. The research was conducted in September 2014 – February 2015. The research was non factorial experiment that arrangge by Randomized Complete Design (RAL) with treatment control, M1 (15 kg of organic mulch/plant), M2 (30 kg organic mulch/plant), and M3 (45 kg organic mulch/plant). The results showed that application of an organic mulch MB with more increasing dose resulted more increasing of pH value, C-organic, N-total, KTK, KB and root growth.   Keywords: organic mulch, Dystrudepts, Mucuna bracteata